Behavioral Analysis of Soccer Players' Motivation Toward Smartwatch Use - Tri Lathif Mardi Suryanto; Nur Cahyo Wibowo; Achmad Afandi; Muhammad Rafi Pratama (Nusantara Science and Technology Proceedings, 2022)
Wear application is one of the most widely used technologies by society. One of them that is widely used by the digital community today is the Smartwatch. Smartwatches are popular with the public because they provide various benefits, ranging from health, and body fitness, to fashion. The benefits of smartwatches do not stop at daily needs but can also be used in sports. In this study, this study aims to measure the motivation of soccer players in using smartwatches to record their performance on the field and daily. This quantitative study uses the conceptual model of TAM and UTAUT which is adapted to a case study of soccer players. The results of this study are Ease of Use, Enjoyment, Attitude Relative Advantage, and Social Influence are conditions that affect soccer players using smartwatches.